1993
DOI: 10.1084/jem.177.4.1105
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the humoral responses to Cryptococcus neoformans infection and glucuronoxylomannan-tetanus toxoid conjugate immunization.

Abstract: Suml'naryThe molecular characteristics of the humoral immune response to a serotype A Cr~tococcus neoformans infection were compared with the response elicited by a cryptococcal ghicuronoxylomannan-tetanus toxoid (GXM-TT) conjugate. Anticryptococcal monoclonal antibodies (mAbs) isolated from both responses have previously been shown to recognize the same antigenic determinant of cryptococcal GXM. Southern blot and sequence analyses indicate that the hybridomas isolated from each response arose from only a few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(193 citation statements)
references
References 81 publications
8
185
0
Order By: Relevance
“…mAb 18B7 Sequencing-Since the 18B7 mAb to GXM was initially isolated and characterized, several studies over the intervening years have found nucleotide and amino acid sequences for the V region containing discrepancies at a number of positions in both H and L chains (24,37,38). These earlier sequences were obtained by either direct mRNA sequencing of the hybridoma cell line or by sequencing cDNA generated by the hybridoma through RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…mAb 18B7 Sequencing-Since the 18B7 mAb to GXM was initially isolated and characterized, several studies over the intervening years have found nucleotide and amino acid sequences for the V region containing discrepancies at a number of positions in both H and L chains (24,37,38). These earlier sequences were obtained by either direct mRNA sequencing of the hybridoma cell line or by sequencing cDNA generated by the hybridoma through RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in our laboratory have led to the development of a murine monoclonal antibody (mAb) library against glucuronoxylomannan (GXM), the major component of the polysaccharide capsule in the fungal pathogen Cryptococcus neoformans (23)(24)(25)(26)(27). Earlier studies suggested that two of these mAbs, 3E5 and 18B7, possess hydrolytic activity against a peptide antigen mimetic known as P1 (28,29).…”
mentioning
confidence: 99%
“…44 -46 This may allow C. neoformans to evade the host defense mechanisms, thus explaining the poor and delayed inflammation usually associated with cryptococcal meningitis 18,47 and the apparent inefficacy of the spontaneous antibody response that we know is based on a restricted repertoire. 48,49 In any case, the ability of C. neoformans to undergo active and rapid antigenic variability should be kept in mind for the future development of immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The 18B7 V H and V L nucleotide sequences have been previously reported based on direct mRNA sequencing (12). The 18B7 V H and V L region cDNA was cloned from 18B7 hybridoma cells by RT-PCR and inserted into human Ig expression vectors as described (8).…”
Section: Region Sequencesmentioning
confidence: 99%